(untitled) (Andamios, Revista de Investigación Social, 2012)
Considering the importance that represents the study of identities processes involved in the development of social protests, the present article sets two objectives. On the one hand, to make visible the main difficulties of the study above-mentioned from the point of view proposed by North-American theories. And, on the other hand, to identify the contributions of the hegemony theory elaborated by Ernesto Laclau for the analysis of the social protest. In this way, the intention is to show the potentialities of the latter perspective in relation to the theories considered dominant in the field of study of collective action.